Records Committee review for rare bird sighting for Eskimo Curlew at Northern Iowa in 1874 - Iowa Ornithologists' Union Records Committeeet al (1933)
Records Committee review for a Eskimo Curlew at Northern Iowa on April 20, 1874. Includes a record review document with votes, the original sighting record found in the publication Extinct birds in Iowa collections in Iowa Bird Life 3:28-29 by Philip A. DuMont seen by S.C. Bowman, and referenced by another publication. Epson - sheet feed